Contribution to the recent trends for surgical management of tendon injuries in equine - Khaled Mohammed Ali Mohammed; Faisal Abdelsamad Torad; Ibrahim Mohamed Ibrahim; Inas Nabil Elhussieny (Cairo : Khaled Mohammed Ali Mohammed, 2011)
Equine lameness due to soft tissue disorders commonly occurs in the forelimbs, particularly involving the palmar metacarpal tendons and ligaments. Ultrasonographic diagnosis has proved highly popular as an easy, safe, non-invasive method of detecting these lesions, permitting not only their morphologic evaluation but, more importantly, their observation over time
Thesis (M.Sc.) - Cairo University - Faculty of Veterinary Medicine - Department of Surgery-Anesthesiology and Radiology
Issued also as CD
Keywords: Equine; Recent trends; Tendon injuries